Antithrombotic property of an aqueous extract from Pseudocedrela kotschyi and Adenia cissampeloides - Wilson Bright Nyansah; George Asumeng Koffuor; Inemesit Okon Ben; Linda Gyanfosu; Ben Enoluomen Ehigiator (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: An aqueous extract from the root bark of Pseudocedrela kotschyi and aerial parts of Adenia cissampeloides has been proven in previous research to elicit significant anticoagulant property in vitro. This, therefore, indicates the potential usefulness of this extract in managing thromboembolic disease, a major global health risk. The aim of the present work was to establish the antithrombotic effect of a product made from extracts of the root bark of P. kotschyi and the aerial parts of A. cissampeloides (PAE). Experimental approach: The effect of PAE at 500-2000 mg/kg in inhibiting tail infarction and inflammation, as well as its effect on the microthrombi count, hematological, and coagulation profiles in a carrageenan-induced thrombosis model in Sprague-Dawley rats, was studied. Findings/Results: PAE significantly (P ≤ 0.01-0.001) reduced length of tail infarction and inflammation (redness, swelling, pain, and temperature). Histopathological studies revealed a significant reduction (P ≤ 0.0001) in microthrombi count in the liver and the lungs with PAE treatment. PAE treatment caused a marginal (P ≤ 0.01) increase in prothrombin time but resulted in a significant (P ≤ 0.01-0.0001) dose-dependent increase in activated partial thromboplastin time, with the hematological profile being normal. Conclusion and implications: PAE showed anticoagulant and antithrombotic effects in vivo, indicative of its potential benefit as a natural product, and cost-effective therapeutic option, and hence could be helpful in thromboembolic therapies.